Immunoexpression of cytokeratin 19 in oral swab from fixed orthodontic appliance users - Ramdhini, Dwi Mutia; Widyaputra, S. Sunardhi; Dardjan, Murnisari (Universitas Padjadjaran, 2007)
The use of fixed orthodontic appliances can improve someone's mastication, speech and appearance. However, this appliance acts as a strange object that may cause irritation to the mucosa epithelial of oral cavity, because of the friction and pressure from the components of the fixed orthodontic appliances which are in direct contact with the oral mucosa. Irritation in the oral mucosa could stimulate the increase of cytokeratin. The appearance of cytokeratin is then used to identify the condition of these cells. This study was a descriptive research to find the expression of cytokeratin 19 with immunohistochemical method in oral mucosa epithelial of fixed orthodontic appliances users. Sample in this study was chosen from 30 fixed orthodontic appliances users. The result of this study was determined by calculating the number of positive cells (brown), compared with total number of cells. The account of positive cells would present the reaction of the epithelial cells according to the inflamation stage which caused by the use of orthodontic appliances. As a conclusion of this study, the use of fixed orthodontic appliances may cause changes in epithelial mucosa which form an adaptation process by increasing the number of progenitor cells marked by cytokeratin 19.